Perancangan Sistem Informasi E-Booking Jasa Steam Mobil Dan Motor Berbasis Web (Studi Kasus Cheers Autocare Solo) - Yunus Yunus Anis; Sunardi; Purwatiningtyas; Arlamsyah Sendi Rifa (Bulletin of Information Technology (BIT), 2023)
In the Big Indonesian Dictionary, booking / ordering is the process of making, how to order (place, goods and so on) to other people. Every year the use of motorized vehicles always increases. This is evident from the data obtained through the Central Bureau of Statistics, namely as many as 136,320,000 million units in 2020. This research uses a qualitative research method which has several stages and flows, namely conducting field studies/observations, interviews, library research, and collecting data and developing software with the Waterfall method. This method is often interpreted as a classic life cycle which is an illustration of a systematic approach and sequential development of software, starting from the specifications required with several stages. The conclusion is that the design of the web-based Steam E-booking information system is in accordance with what is needed by Cheers. Autocare Solo, the results and tests are in accordance with user needs, the database used contains 6 tables, namely: admin, category, service, booking, complaint, customer reports, and Information System Design E-booking Steam car and motorbike services help make it easier for the company . The design of the web-based Steam E-booking information system is in accordance with what is required by Cheers Autocare Solo, the results and tests are in accordance with user needs and help make it easier for the company